ERCP-related complication is not the only cause of GI bleeding in post-liver transplantation patients: A case report. Issue 37 (September 2017) - Ding, Zhen; Tang, Xue-Lian; Lin, Rong; Han, Chaoqun; Liu, Jun
Abstract: Rationale: Endoscopic retrograde cholangiopancreatography (ERCP) is the treatment of choice for biliary complications in liver transplantation (LT) recipients as it is both diagnostic and therapeutic. The specific risks following ERCP among LT recipients have not been well studied. Patient concerns: A 56-year-old man with a history of orthotopic LT underwent endoscopic retrograde cholangiopancreatography (ERCP) as a treatment of biliary strictures, whereby a plastic stent was implanted. Thirteen days after ERCP the patient developed multiple episodes of hematemesis. Diagnosis: Digital subtraction angiography (DSA) of the hepatic artery and superior mesenteric artery showed a hepatic pseudoaneurysm (PA) in the left hepatic artery. The final diagnosis was bleeding from the PA. Intervention: Interventional embolization of the branch with PA was performed to stop the bleeding. Outcome: The patient remained free of GI bleeding for 25 days after interventional embolization, but he developed another bout of bleeding and unfortunately passed away. Lessons: ERCP-related complication is not the only cause of post-ERCP bleeding, and that other primary causes should also be ruled out.